2023
DOI: 10.3390/molecules28052162
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid-Caused Quenching Effect of Protein Clusteroluminescence Probe: The Fast Fluorescent Detection of Ascorbic Acid in Vegetables

Abstract: It is interesting and meaningful to explore fluorescent probes for novel rapid detection methods. In this study, we discovered a natural fluorescence probe, bovine serum albumin (BSA), for the assay of ascorbic acid (AA). Due to clusterization-triggered emission (CTE), BSA has the character of clusteroluminescence. AA shows an obvious fluorescence quenching effect on BSA, and the quenching effect increases with increasing concentrations of AA. After optimization, a method for the rapid detection of AA is estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…[31] The low LOD suggests that Eu-NDBC is sensitive enough to alarm low plasma AA for some AAconcerning diseases. Compared to those reported AA fluorescence sensors (Table 1), the sensitive Eu-NDBC with LOD of 4.53 μM is lower than or comparable to those μM-level LODs, such as bovine serum albumin (6 μM), [32] terbium(III) chelating with 1,10-phenanthroline (74 μM), [33] CD-Fe 3 + (5 μM), [34] CsPbBr 3 / BSA NCs (28 μM), [35] CD-QD@SiO 2 (3.17 μM), [36] Cel-Au NCs (2.5 μM), [37] RhB@Tb-MOFs (2.54 μM) [38] and NF CDs (4.22 μM). [39] However, LOD of 4.53 μM is higher than those nM-level LODs, such as Cys-Au NCs (2.43 nM), [40] ProN6 (77.9 nM), [41] CNCs (0.15 nM), [42] and MN-CDs (0.03 μM).…”
Section: Fluorescence Detection Of Eu-ndbc Sensing Aamentioning
confidence: 63%
“…[31] The low LOD suggests that Eu-NDBC is sensitive enough to alarm low plasma AA for some AAconcerning diseases. Compared to those reported AA fluorescence sensors (Table 1), the sensitive Eu-NDBC with LOD of 4.53 μM is lower than or comparable to those μM-level LODs, such as bovine serum albumin (6 μM), [32] terbium(III) chelating with 1,10-phenanthroline (74 μM), [33] CD-Fe 3 + (5 μM), [34] CsPbBr 3 / BSA NCs (28 μM), [35] CD-QD@SiO 2 (3.17 μM), [36] Cel-Au NCs (2.5 μM), [37] RhB@Tb-MOFs (2.54 μM) [38] and NF CDs (4.22 μM). [39] However, LOD of 4.53 μM is higher than those nM-level LODs, such as Cys-Au NCs (2.43 nM), [40] ProN6 (77.9 nM), [41] CNCs (0.15 nM), [42] and MN-CDs (0.03 μM).…”
Section: Fluorescence Detection Of Eu-ndbc Sensing Aamentioning
confidence: 63%
“…These results show that the reaction with BSA may be the reason for the decrease in CsPbBr 3 /BSA NCs fluorescence caused by AA, while the mechanism of the reaction needs to be researched further, given there are few studies on AA and BSA reactions to date. In addition, the possible mechanism of AA induced fluorescence quenching of CsPbBr 3 /BSA NCs may be due to the electrostatic interaction between AA and BSA, according to the reported literature [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…104 Han et al used bovine serum albumin as a natural protein cluster fluorescent probe to achieve a simple, rapid, sensitive, efficient and selective detection of the essential micronutrient ascorbic acid (vitamin C). 105 Zhang et al utilized nonconjugated poly(maleimide)s (PMs) for fingerprint detection by sensing proteins and amino acids. 39 As the luminescence characteristics of NCLMs are intimately related to the molecular-scale motion and aggregation state they can be used as efficient fluorescence detectors to visualize the polymerization/emission process.…”
Section: Room-temperature Phosphorescence (Rtp)mentioning
confidence: 99%
“…Qin et al prepared a series of biobased furfural polyamides and demonstrated their use as probes for the selective recognition of Fe 2+ and Fe 3+ in aqueous solution with high sensitivity compared to other metal ions, by a fluorescence quenching effect . Han et al used bovine serum albumin as a natural protein cluster fluorescent probe to achieve a simple, rapid, sensitive, efficient and selective detection of the essential micronutrient ascorbic acid (vitamin C) . Zhang et al utilized nonconjugated poly­(maleimide)­s (PMs) for fingerprint detection by sensing proteins and amino acids …”
Section: Macromolecules With Nonconventional Luminescencementioning
confidence: 99%
See 1 more Smart Citation